2021
DOI: 10.3390/su132313428
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Effects of Antimicrobials Drugs in Aquatic Ecosystems

Abstract: Currently, thanks to the development of sensitive analytical techniques, the presence of different emerging pollutants in aquatic ecosystems has been evidenced; however, most of them have not been submitted to any regulation so far. Among emerging contaminants, antimicrobials have received particular attention in recent decades, mainly due to the concerning development of antibiotic resistance observed in bacteria, but little is known about the toxicological and ecological impact that antimicrobials can have o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Several studies revealed the significance of antimicrobial drugs on aquatic organisms [83,84]. For example, the parental exposure of marine fish (Oryzias melastigma) to sulfamethazine (4.62 mg × g −1 ) may negatively affect the growth performance in adults [14,85].…”
Section: The Effect Of Single and Combined Stressors On The Life Hist...mentioning
confidence: 99%
“…Several studies revealed the significance of antimicrobial drugs on aquatic organisms [83,84]. For example, the parental exposure of marine fish (Oryzias melastigma) to sulfamethazine (4.62 mg × g −1 ) may negatively affect the growth performance in adults [14,85].…”
Section: The Effect Of Single and Combined Stressors On The Life Hist...mentioning
confidence: 99%
“…Since the late 1990s, antibacterials have received particular attention due to their detection in surface and coastal waters and concerns about the emergence of antimicrobial resistance. High consumption and low absorption by humans and animals have caused them to be discharged to soil and receiving waters in their different manufacturing, consumption and disposal processes, with or without pretreatment in wastewater treatment plants becoming present in aquatic ecosystems at concentrations at the ng L − 1 range (Bojarski et al, 2020;da Le et al, 2021;Felis et al, 2020;Fernandez et al, 2021;Kovalakova et al, 2020). Although advanced oxidation processes and other treatments such as membrane bioreactors, bioelectrochemical systems and constructed wetlands have proven to be efficient for the removal of these compounds, they are not frequently used (Fernandez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…High consumption and low absorption by humans and animals have caused them to be discharged to soil and receiving waters in their different manufacturing, consumption and disposal processes, with or without pretreatment in wastewater treatment plants becoming present in aquatic ecosystems at concentrations at the ng L − 1 range (Bojarski et al, 2020;da Le et al, 2021;Felis et al, 2020;Fernandez et al, 2021;Kovalakova et al, 2020). Although advanced oxidation processes and other treatments such as membrane bioreactors, bioelectrochemical systems and constructed wetlands have proven to be efficient for the removal of these compounds, they are not frequently used (Fernandez et al, 2021). Most countries use conventional depuration processes (activated sludge, sequenced batch reactors and anaerobic digestion processes) that have low antimicrobial removal rates ( Ávila et al, 2021;Fernandez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations